Singlet oxygen imaging in polymeric nanofibers by delayed fluorescence - Mosinger, Jiří; Lang, Kamil; Hostomský, Jiří; Franc, Jiří; Sýkora, Jan; Hof, Martin; Kubát, Pavel (The journal of physical chemistry. B, 2010)
Polymeric nanofiber materials loaded with photosensitizers exhibit significant antibacterial activity due to their generation of cytotoxic singlet oxygen O(2)((1)Δ(g)). A time-gated fluorescence imaging technique was used to monitor the photosensitized processes in polystyrene (PS) and gelatin (GE) nanofibers loaded with 0.1 wt % tetraphenylporphyrin (TPP) photosensitizer. The fluorescence decay of TPP at the periphery of the PS nanofibers was single exponential. Increased fluorescence quenching was observed in the domains with higher TPP loading, located in the center of the nanofibers, and added a shorter lifetime component to the kinetics. The domains exhibiting singlet oxygen activity within the nanofibers were visualized and analyzed by singlet oxygen-sensitized delayed fluorescence imaging (SODF). Whereas O(2)((1)Δ(g)) was produced in PS nanofibers, its production in GE nanofibers was limited. These results were confirmed by time-resolved phosphorescence measurements at 1270 nm.
Keywords: velikost částic; povrchové vlastnosti; Polymers; Singlet Oxygen; Nanofibers; Surface Properties; fluorescenční mikroskopie; nanovlákna; fluorescence; polymery; singletový kyslík; Microscopy, Fluorescence; Fluorescence; Particle Size; Time Factors; časové faktory